Recruiting ESCRT to single-chain heterotrimer peptide MHCI releases antigen-presenting vesicles that stimulate T cells selectively - Blade A. Olson; Kathryn E. Huey-Tubman; Zhiyuan Mao; Magnus A. G. Hoffmann; Pamela J. Bjorkman; Richard M. Murray; Stephen L. Mayo (Proceedings of the National Academy of Sciences, 2025)
Immune cells naturally secrete extracellular antigen-presenting vesicles (APVs) displaying peptide:MHC complexes to facilitate the initiation, expansion, maintenance, or silencing of immune responses. Previous work has sought to manufacture and purify these vesicles for cell-free immunotherapies. In this study, APV assembly and release is achieved in nonimmune cells by transfecting a single-chain heterotrimer (SCT) peptide major histocompatibility complex I (pMHCI) construct containing an ESCRT- and ALIX-binding region (EABR) sequence appended to the cytoplasmic tail; this EABR sequence recruits ESCRT proteins to induce the budding of APVs displaying SCT pMHCI. A comparison of multiple pMHCI constructs shows that inducing the release of APVs by the addition of an EABR sequence generalizes across SCT pMHCI constructs. Purified pMHCI/EABR APVs selectively stimulate IFN-γ release from T cells presenting their cognate T cell receptor, demonstrating the potential use of these vesicles as a form of cell-free immunotherapy.